TEACHING AND LEARNING STRATEGIES PRACTICED BY LANGUAGE TEACHERS TO ACTIVELY ENGAGE THEIR STUDENTS IN LEARNING - Ida Bagus Nyoman Mantra; Ida Ayu Made Sri Widiastuti; I Nyoman Suparsa; Nengah Dwi Handayani (International Journal of Applied Science and Sustainable Development (IJASSD), 2020)
Teaching strategies are techniques used by teachers to help students become independent in learning and active strategic learners. Teaching strategies become learning strategies when students independently choose suitable ones and practice them effectively to achieve tasks or meet their learning goals. This study aims to examine the learning strategies applied by language teachers in language learning practices in the classroom to optimize students’ language skill acquisition. Data collection methods used are observation, interview, and documentation. The data analysis technique is descriptive qualitative analysis, namely data reduction, presentation, and concluding. The results showed that there are several favorable teaching strategies employed by language teachers to improve students' language skills. This research has implications for educational institutions to continually improve teachers’ skills to implement effective and innovative learning strategies.